2007
DOI: 10.1111/j.1600-0714.2007.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an in vivo mouse model to study oral submucous fibrosis

Abstract: The study provides further evidence that areca nut contributes to the development of OSF in treated animals. The model has the potential to test synergism of areca nut with other carcinogens and any therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 33 publications
(41 reference statements)
0
36
0
Order By: Relevance
“…Table 2 -shows the association between OSMF with gutkha and arecanut. Study subjects who had gutkha only (58) were more as compared to arecanut + tobacco (28). The difference was found to be statistically significant (p=0.05).…”
Section: Resultsmentioning
confidence: 41%
See 1 more Smart Citation
“…Table 2 -shows the association between OSMF with gutkha and arecanut. Study subjects who had gutkha only (58) were more as compared to arecanut + tobacco (28). The difference was found to be statistically significant (p=0.05).…”
Section: Resultsmentioning
confidence: 41%
“…[12][13][14][15][16][17][18][19][20][21] Chewing tobacco alone and smoking are not considered to play a role in the development of this disease, [8,11,[15][16][17] it has been conclusively proven that OSMF occurs because of areca nut consumption and is not associated with tobacco. [2][3][4]8,17,[21][22][23][24][25][26][27][28][29][30] Keeping the above points in view the present study was carried out with the aim to correlate the severity of OSMF with duration and frequency of areca nut and its product chewers.…”
Section: Introductionmentioning
confidence: 99%
“…In that model, the buccal mucosa was treated twice daily 6 days per week with a topical application of aqueous ANE for 300–600 days. The authors of the study demonstrated that after only 600 days of treatment, the fibrotic scores for cellularity, inflammation and muscle atrophy were significantly different from those of the control group [22]. However, this model is time-consuming and requires almost the entire life span of a mouse to induce OSF.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, Sumeth Perera and coworkers demonstrated that after 300 to 600 days of ANE application twice daily to the buccal mucosa of mice, OSF development could be observed [22]. However, the establishment in one month of bleomycin-induced dermal fibrosis in mice via SC injection has been well established [23].…”
Section: Introductionmentioning
confidence: 99%
“…The characterizations of these models were not complete and the experimental evidence was neither convincing nor reproducible. The relevance of a particular animal model to a human disease rests on its ability to parallel the biological changes that characterize the disease in humans Perera et al 45 described an OSF animal model in female albino mice of BALB/c strain. They applied an aqueous areca nut extract prepared from fresh, mature endosperms of Areca catechu…”
Section: Experimental Animal Studiesmentioning
confidence: 99%